Unraveling the Roots: Investigating Etiological Patterns of Acute Kidney Injury in Hospitalized Patients at Khyber Teaching Hospital, Peshawar, Pakistan - Raza, Ali; Suhail, Samra; Muhammad Noman; Nisa, Ulfat; Khattak, Aaliyan; Banaras, Faizan (Indus Journal of Bioscience Research, 2024)
Background Acute kidney injury (AKI) is the main cause of poor outcomes for patients. AKI affects about 13.3 million individuals worldwide annually with eight-five percent living in nations that are developing. Methodology It was a cross-sectional study. 74 patients were included in the study. AKI was diagnosed using the RIFLE criteria, based on serum creatinine levels. Hospital acquired acute kidney injury (HAAKI) was defined as the onset of AKI occurring any time after 48 hours of hospitalization in patients who were admitted with normal renal function. Data was collected from patient records, such as demographics, and clinical history. Variables were reported as mean ± SD. Statistical calculation was done using Chi‐square test. P < 0.05 was considered significant. All the calculations were carried out with the help of software IBM SPSS STATISTICS 25 version. Results This study underscores the impact of HAAKI on patient outcomes, affecting all age groups, with a majority of cases among individuals under 50. The findings highlight infections and trauma, notably sepsis and hypotension, as major causes, making up over two-thirds of HAAKI cases. The severity of kidney injury, classified by the RIFLE criteria, was directly correlated with increased mortality and the need for dialysis, especially for patients in the "Failure" category. Survival outcomes were notably higher for those in the "Risk" stage compared to the "Injury" and "Failure" stages, which experienced higher mortality. This emphasizes the necessity for early detection and management of patients with progressing kidney injury to prevent progression to critical stages. Timely intervention could potentially reduce mortality and improve overall outcomes for HAAKI patients. Conclusion This study highlights HAAKI has significant impact on patient outcomes, showing that sepsis and hypotension are major causes. Mortality risk escalates with RIFLE category severity, particularly in the “Failure” stage. Early identification and proactive management are essential to reduce progression, improve survival, and enhance patient outcomes in HAAKI cases.